Kontekstualisasi Kitab Ayyuha al Walad: Pengarusutamaan Konsep Pendidikan Karakter Imam Al-Ghazali di Era Modern - Muchammad Nur Huda (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2021)
Character education is a concept of educational goals that have been presented by Islamic education leaders for a long time, but in this era, it is increasingly being abandoned. One of them is al-Ghazali, his thoughts on education oriented to the character and morality of students have made a positive contribution to the realm of educational goals in general. The methodology used is library research, with a descriptive-qualitative approach. Several findings in the concept as outlined in his work Ayyuha al-Walad. This book reveals a lot of his advice to his students who asked for special notes as a provision for amaliyyah in his life. It turns out that the written advice contains a lot of messages in the form of characters that must be possessed and carried out by someone knowledgeable, a giver of knowledge, and a student of knowledge. these three subjects must have the ultimate goal of attaining faith and closeness to Allah.